A case study analysis : Oversea-Chinese Banking Corporation Limited / Azmi Sulaiman, Arafat Ibrahim and Mohd Sophy Ahmad - Sulaiman, Azmi; Ibrahim, Arafat; Ahmad, Mohd Sophy (Faculty of Business and Management, 2001)
The economic downturn that stroked this region had shattered the banking industry in which led to the collapsing of many banks in Malaysia. From this situation it has inspired us to investigate several banks which has been chosen to the effect of the current situation. OCBC Bank was chosen as the main bank with it's competitors Malayan Banking Berhad and RHB Berhad in this study. The main question to be investigated is how OCBC maintain its competitiveness in the banking industry in Malaysia despites the current situation and several other factors internally and externally. How it's strategist reacted towards the strict regulations and rules imposed by Malaysian government. The question of it's surviving strategies to overcome the competition as a foreign banks among Malaysian anchor banks such as Malayan Banking Bhd. and RHB Bhd.